Partnership between librarians and faculty at a Malaysian university library: a focus group survey - Abu Bakar, Ahmad Bakeri (University of Nebraska--Lincoln Libraries, 2009)
This study examines the changes in the way the information services are delivered to faculty. One of the delivery methods for faculty adopted by most academic libraries in Malaysia is a liaison programme. In this programme, a reference librarian is appointed as a liaison librarian to one or more teaching departments. Online resources have made faculty less reliant on the partnership of a liaison programme for help with teaching and research, while electronic communication, such as email, has the potential to make the partnership more lasting and effective. The study reveals that liaison librarians must upgrade their competencies to perform up to the level demanded by faculty. They must also promote library services, collaborate, and maintain good rapport with faculty.